Internet, democracia e eleições : as cibercampanhas presidenciais brasileiras em 2006 - Iasulaitis, Sylvia (Universidade Federal de São Carlos, 2008)
This dissertation has the general objective of contributing to the theoretical and empirical comprehension of the implications of the internet for democracy and electoral processes. We analyze the cyberparadigms and the normative assumptions that influenced thematic production. The adopted analytical standpoint aims to apply the premises deriving from the theoretical apparatus of reference to a concrete empirical context, trying to balance the strong normative assumptions and overcome the notion of technological determinism present in much of the literature. This way, we delimit the way the internet is being used in electoral processes, its possibilities and limits, promoting an adaptation of expectations. We use a critical approach to be able to scrutinize the potential of the internet in reinvigorating democracy and its processes and exploring its actual conditions of production in specific political-electoral contexts, bringing elements of political culture to the center of the debate. For this analysis we used a systematic empirical base and a temporal specification: the Brazilian political-electoral context during the presidential race of 2006. The objects of investigation in a comparative perspective were the websites of the two main candidates for the Presidency of the Republic in the 2006 contest: Luiz Inácio Lula da Silva (PT) and Geraldo Alckmin (PSDB). Specifically, the empirical investigation was guided by the following research queries: 1) What are the functions and possibilities of interaction and participation in electoral websites? 2) Are there differences between the websites of the Alckmin and Lula campaigns in terms of sophistication and design that indicate different levels of professionalism? 3) What are the strategies of the cybercampaigns? 4) According to the options on offer, what is the main targeted public of the websites? This investigation began from four hypotheses: 1) the electoral websites will reflect more the function of top-down and one-way, neglecting the interactive possibilities of the new media in promoting dialogue with the electorate; 2) there will be convergence and standardization, instead of differentiation between parties, in the way of usage of the Brazilian political websites; 3) the online strategy will be centered more in attracting predisposed and politically active constituents, as well as grabbing the attention of media professionals, then apathetic and demobilized citizens, and finally 4) the Internet will be an important space for negative campaigning on part of Alckmin, due to his position of challenger in the contest and due to the political context that preceded the electoral race, highly scarred by accusations of corruption, as well as legal loopholes in relation to the internet. The reelection candidacy of President Lula will be centered in the publication of endorsements and in the retrospective strategy of incorporating symbols of the post of president and exploring actions of his first term in office. The methodological strategy adopted is based on the research design of Content Analysis of websites, applied on three levels of analysis: functional, formal, and content of the clippings and persuasive strategies of the candidates. These analytical dimensions are composed by indicators, typologies, and many categories that comprise diverse dichotomous variables.
Keywords: Internet (Redes de computação); Brasil - campanha eleitoral; Campanha eleitoral; Ciberdemocracia; Pleito presidencial 2006; Campanhas políticas profissionalizadas; Internet; Electoral communication; Professionalized political campaigns; Cyberdemocracy; Brazilian presidential contest 2006; OUTROS::CIENCIAS SOCIAIS